Mediating the divine : prophecy and revelation in the Dead Sea scrolls and Second Temple Judaism - Jassen, Alex P. (Studies on the texts of the desert of Judah, 2007)
This book is a comprehensive treatment of prophecy and revelation in the Dead Sea Scrolls. It begins by analyzing the re-presentation of the classical prophets and their revelatory experience in an attempt to identify how prophecy and revelation was reconceptualized in the Dead Sea Scrolls in dialogue and in contrast with received biblical models. This work then examines the direct evidence in the Dead Sea Scrolls regarding ongoing prophetic activity at Qumran and in related segments of Second Temple Judaism. This study argues that the Dead Sea Scrolls bear witness to a transformed prophetic tradition active at Qumran and in Second Temple Judaism. Topics treated include the relationship of prophecy to scriptural interpretation, wisdom, and law, and eschatological prophecy.